Broad Thermal Tolerance in the Cold-Water Coral Lophelia pertusa From Arctic and Boreal Reefs - Dorey, Narimane; Gjelsvik, Øystein; Kutti, Tina; Büscher, Janina V. (Frontiers in Physiology, 2020)
Along the Norwegian coasts and margins, extensive reefs of the stony coral Lophelia pertusa act as hotspots for local biodiversity. Climate models project that the temperature of Atlantic deep waters could rise by 1-3°C by 2100. In this context, understanding the effects of temperature on the physiology of cold-water species will help evaluating their resilience to future oceanic changes. We investigated the response of L. pertusa to stepwise short-term increases in temperature. We sampled corals from four reefs, two located north of the Arctic circle and two at the mid-Norwegian shelf (boreal). In on-board experiments (one per reef), the sampled fragments were exposed to increasing temperatures from 5 to 15°C over 58 h. Respiration increased linearly by 3-fold for a 10°C increase. The short-term temperature increase did not induce mortality, or cellular (Neutral Red Assay for lysosome membrane stability; but one exception) or oxidative stress (Lipid Peroxidation Assay). However, the variability of the respiration responses depended on the experiment (i.e. reef location), possibly linked to the genetic structure of the individuals that we sampled (e.g. clones or siblings). The corals from the Arctic and boreal regions appear to have a high tolerance to the rapid temperature fluctuations they experience in the field. Over extended periods of time however, an increased metabolism could deplete the energy stored by the corals, if not met by an increased food availability and/or uptake. Empirical data on organisms’ thermal performance curves, such as the one presented in this study for L. pertusa, will be useful to implement predictive models on the responses of species and populations to climate change.